Power masking and different frequency reuse schemes in 4G OFDMA downlink - Hoang, Thanh Long. (2012)
Modern 4G OFDMA-based networks are supposed to provide high data rate access to users. In such networks, strong co-channel inference at cell edge is the key issue that dramatically degrades quality of services in the area. Several novel frequency reuse schemes have been proposed and studied with the aim of solving the problem. In this work, those schemes were investigated using a practical simulation model assuming that traffic was crowded. The dependence of blocking and dropping probabilities versus user’s data rate of different schemes was considered. The performance of those frequency reuse schemes was compared. It is shown that while most of them enhanced QoS and fairness in the system, some even made the situation worse.